Why the Bath Profile Makes Z39.50 Work - Gethin, Peter (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
The Z39.50 standard has been in productive use for several years now. However, due to the way the standard has been interpreted by some Integrated Library System (ILS) vendors, the results of using the standard have often been somewhat varied at best and, at worst, non functional. The lack of consistency in the use of Z39.50 has lead to the standard being held in rather lower regard than it deserves in some quarters. It is a matter that can be debated whether the inconsistency in the implementation of the standard is the fault of the implementers ignoring aspects of the standard to make their task simpler or simply a lack of precision in the standard itself. To circumvent the debate, the Z39.50 Implementers Group (ZIG) has defined profiles for the use of the standard that are clearly defined and can be measured. This paper takes a look back at why the Z39.50 standard was invented in the first place and defines briefly how Z39.50 works. The paper then considers why implementations of the standard appear to fail and how those failures manifest themselves. With this information in hand, it is possible to make sense of the answer to the question, how does the Bath profile make Z39.50 work?